Do Labor Market Policies and Growth Fundamentals Matter for Income Inequality in Oecd Countries? : Some Empirical Evidence - Van Houdt, Patrick (IMF Working Papers; Working Paper ;, 1997)
Income distribution may be related to fundamentals affecting economic growth and to labor market policies. Noting that inequality is affected by unemployment. This paper presents a model in which labor market policies affect unemployment which in turn affects inequality. The model also includes the effects of changes in per capita income on inequality through the accumulation of physical capital and technological know-how. When a resulting reduced-form relationship is estimated, its explanatory power is surprisingly high: on average, it explains about three quarters of the variation in inequality measures for the OECD countries, and Granger Causality tests confirm the model's predictions.